The Representation of Sexism in A Textbook Entitled “English in Mind” - Taufik, Taufik Hidayat; Utami Asity, Yuni; Hermagustiana, Istanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The result of this research explains the representation of sexism based on three English textbooks “English in Mind”. The focus of this research is to investigate the frequency of males and females, the representation of males and females in occupational roles, and the representation of males and females as inspiring persons based on pictures and reading texts. Thus, the study implements Fairclough's three-dimensional discourse approach: description, interpretation, and explanation for textbook analysis. The study revealed that the frequency of males and females was based on text and pictures. The male is more dominant than the female. Furthermore, males and females in this textbook were portrayed as having the power to do outdoor activities. As well, the female is not only portrayed as the housewife or taking care of the baby. Otherwise, the representation of males and females as inspiring persons variation sometimes comes to an unfamiliar person. Males were superior to females according to the frequency in three English textbooks “English in Mind”. However, the study educates to students be aware of sexism issues in real life, and also students have a perception that being stronger or more capable in some activity does not only refer to gender.